Development without aid : the decline of development aid and the rise of the diaspora - Phillips, David A., 1946- (London : Anthem Press, 2013)
'Development without Aid' opens up perspectives about foreign aid to the world's poorest countries. Growing up in Malawi the author developed a sense of the limitations of foreign assistance and from this evolves a critique of foreign aid as an alien resource unable to provide the dynamism that could propel the poorest countries out of poverty.[NP] The book aims to help move the discussion beyond foreign aid. It examines the rapid growth of the world's diasporas as a quasi-indigenous resource of increasing strength in terms of both financial and human capital, and considers how far such a resource might supersede aid. It uses extensive research findings to explore the possibilities for a resumption of sovereignty by poor states, especially in Africa, over their own development with the assistance of the world's diasporas.
List of acronyms -- Acknowledgments -- Preface: motivation and perspective -- What is foreign aid, who does it, why and how much is there? -- How far has development aid been effective? -- Why has development aid done so little? -- Changing the dynamics of development -- "New aid" : new ways to promote and finance development? -- Another pathway out of poverty? -- Exit strategy : replacing foreign assistance -- Postscript -- Notes -- Index.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Economic assistance -- Developing countries; Developing countries -- Dependency on foreign countries; Developing countries -- Economic conditions